Export Market Size Matters: The effect of the market size of export destinations on manufacturing growth (2022)
Literature contends that the manufacturing sector is crucial for economic development, and it is conventional wisdom that exports drive manufacturing growth. However, it has not yet been established empirically whether the market size of export destinations is an important factor to explain diverging regional and sectorial manufacturing growth patterns. This article argues that accessing large external markets reduces transaction costs, increases expectations of economies of scale and fosters capital formation. To test this hypothesis, we construct a novel Relative Export Market Size (REMS) index that measures whether the share of sectoral exports that are destined to large economies in one region is higher than in other regions. Using a PVAR model, we verify the impact of the REMS index on value added, employment and capital accumulation of 129 manufacturing sectors in 23 regions in Colombia during the period 1992-2017. The obtained results show that exporting to larger markets has a positive impact on employment, capital formation and value added per capita of manufacturing sectors at a regional level. This finding indicates that exporting to the largest market of the world helps to develop competitive manufacturing sectors.